Об интерпретации дифференциальных спектров отражения и поглощения кристаллов сульфида и селенида кадмия - Мовсесян, Г. М.
The interpretation of the differential spectra is connected with the definite difficulties on account of ] specific character of methods. It is shown that for the precise determination of positions of energies offl the resonance exitons only according to the differencial spektra it is necessory to cany out a large number of measurings which permit to discover stable permissive peculiarities according to energy of d the given exiton stripe. It has been conducted the comparison of the outlines of the resonance exitone with the term of the same lines, calculating on the basis of the existent theory and it has been shownl the satisfactory coincidence of the theory with the experiment.
Keywords: Физика